Atlas of the Antarctic deep structure with the Gravimetric Tomography - R. Kh. Greku; P. F. Gozhik; V. A. Litvinov; V. P. Usenko; T. R. Greku (Ukrainian Antarctic Journal, 2009)
Atlas of the Antarctic deep structure with the Gravimetric Tomography / Greku R.Kh., Gozhik P.F., Litvinov V.A., Usenko V.P., Greku T. R.; – Kiev, 2009. – 69 pp. – ISBN 978-966-02-4937-0. The Atlas contains results of a deep structure modeling of the Antarctic and the South Ocean regions. Initial data are spherical harmonics of the EGM96 global geoid model. Dense heterogeneities are calculated using the gravimetric tomography technology. 3D images of vertical and lateral sections on different depths are presented. Proceeding compiling, computer design: “Geographika”.